Northwestwards shift of tropical cyclone genesis position during autumn over the western North Pacific after the late 1990s. (18th October 2019) - Cao, Xi; Liu, Yong; Wu, Renguang; Bi, Mingyu; Dai, Yifeng; Cai, Zelin
Abstract: Previous study has suggested a northwestwards shift of tropical cyclone (TC) genesis position during autumn over the western North Pacific (WNP) after the late 1990s. This study replenishes two mechanisms to explain this inter‐decadal change in the WNP TC genesis position. The first mechanism is related to the mean state change. According to observational analysis and numerical simulations with the Geophysical Fluid Dynamics Laboratory (GFDL) atmospheric general circulation model, a La Niña‐type Pacific sea surface temperature (SST) change and the northern Atlantic Ocean warming in the late 1990s cause a dipole pattern of lower‐level circulation change, with cyclone over the northwestern WNP and anticyclone over the southeastern WNP. This pattern is favourable for more TC genesis in the northwestern WNP. The sensitivity experiments show that the contribution from the Pacific Ocean is larger than that from the northern Atlantic Ocean. The second mechanism is related to the change in the intra‐seasonal oscillation intensity, particularly the quasi‐biweekly variation. The activity of intra‐seasonal oscillations over the southeastern WNP shows a decadal decrease around the late 1990s. Meantime, when the intra‐seasonal oscillations with tilted structure move northwestwards, they provide a favourable condition for TC genesis to be located more northwestwards after the late 1990s. Abstract : Previous study has suggested a northwestwards shift of tropical cyclone (TC) genesis position during autumn over the western North Pacific (WNP) after the late 1990s. This study replenishes two mechanisms to explain this inter‐decadal change in the WNP TC genesis position. The first mechanism is related to the mean state change. According to observational analysis and numerical simulations, a La Niña‐type Pacific sea surface temperature change and the northern Atlantic Ocean warming in the late 1990s cause a dipole pattern of circulation change, with cyclone over the northwestern WNP and anticyclone over the southeastern WNP. The second mechanism is related to the change in the intra‐seasonal oscillation intensity, particularly the quasi‐biweekly variation.